Judges’ Considerations in Settling Crimes of Violence Against Biological Children: An Islamic Criminal Law Perspective - Marlisa, Marlisa; Sufrizal, Sufrizal; Sufyan, Muhammad Suhaili (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
Violence against children in Islam is permissible if it does not exceed the limit. It is also only used as an educational effort, not to punish without reason. Because if children are left free without rules, it will have a bad impact on children. The objectives of this study are: To find out the basis of the judge’s consideration in the decision of case Number 243/Pid.Sus/2020/PN Idi; and to find out the crime of violence against children in the view of Islamic criminal law. The method used is a type of qualitative research with a case approach. The data collection techniques are interviews and documentation. While the first analysis examines and explains theories. Second, looking for answers to the main problem, and third, drawing conclusions that are the end of this research, from general to specific. The results of the research obtained are 1) The incriminating consideration is that the actions of NR’s sister are a very reprehensible, immoral act committed by parents against children, thus causing disability. The mitigating dispute is that NR’s sister has apologized and promised not to repeat her actions, so this decision is ultrapetita; court decisions in cases of violence against children need to consider aspects of Islamic law, national law, and child protection principles. The goal is to ensure justice for victims, prevent future violence, and strengthen the synergy between religious values and state law in protecting children as the next generation of the nation. 2) Islam itself is very clear and firmly prohibits acts of violence, especially against children. The Qur’an, hadith, and scholars also discuss acts of violence against children with various opinions with the same goal, namely, that educating children is the right of parents, with provisions that have been recommended without crossing the limit in terms of education. The state also regulates in terms of educating and nurturing children, namely in Law Number 35 of 2014 concerning Child Protection.